Identification of a novel dual-targeting peptide inhibitor of SARS-CoV-2 RBD and NRP1 through structure-based virtual screening - Yao, Nan; Guan, Lixia; Feng, Li; Wang, Gang; Wang, Yuting; Niu, Miao-Miao; Yu, Mei; Yin, Shengnan (Frontiers in Pharmacology, 2025)
BackgroundThe continuous mutations of SARS-CoV-2 have enhanced its transmissibility and immune escape capabilities. Its invasion into cells relies on the binding of the receptor-binding domain (RBD) of the spike (S) protein to host receptors, while NRP1, as a key host cofactor, promotes viral attachment and internalization by recognizing the S protein. Therefore, dual targeting of RBD and NRP1 represents a potentially effective antiviral strategy.MethodsIn this study, a multi-step screening strategy combining molecular docking, MST assays, molecular dynamics simulations, pseudovirus neutralization assays, MTT assays, and in vivo experiments in mice was used to discover dual-targeting inhibitors of SARS-CoV-2 RBD and NRP1.ResultsFive peptide inhibitors (peptides 1–5) that simultaneously target RBD and NRP1 were identified through structure-based virtual screening. MST assays showed that peptides 1–5 all exhibited nanomolar affinity for both RBD and NRP1, with peptide-1 showing the strongest affinity for RBD (Kd = 19 nM) and NRP1 (Kd = 32 nM). Molecular dynamics simulations indicated that peptide-1 can stably bind to RBD and NRP1 proteins. Importantly, peptide-1 exerted efficient antiviral activity against the SARS-CoV-2 Omicron XBB.1.5 (EC50 = 0.62 ± 0.03 μM) and exhibited no obvious toxicity to normal human alveolar cells. Furthermore, in vivo assays indicated that peptide-1 had effective antiviral activity without severe side effects.ConclusionIn conclusion, peptide-1 is a highly effective and low-toxicity antiviral inhibitor that dual-targets RBD and NRP1.